Dietary Effects of Lipid and Protein Levels on Growth, Feed Utilization, Lipid Metabolism, and Antioxidant Capacity of Triploid Rainbow Trout (Oncorhynchus mykiss) - Yun-Feng Chen; Kai-Lin Cao; Hong-Fei Huang; Xiao-Qin Li; Xiang-Jun Leng (Aquaculture Nutrition)
This study investigated the dietary effects of lipid and protein levels on growth performance, feed utilization, body composition, lipid metabolism, and antioxidant capacity of triploid rainbow trout, Oncorhynchus mykiss. A 3 × 2 two-factor design was conducted with three crude lipid levels of 4%, 9%, and 14% (L4, L9, and L14) and two crude protein levels of 44%, 49% (P44, P49). Therefore, a total of six diets were prepared as P44/L4, P44/L9, P44/L14, P49/L4, P49/L9, and P49/L14. Triploid rainbow trout (initial body weight 65.0 ± 0.1 g) were fed one of the six diets for 80 days. The results showed that weight gain (WG), protein retention (PR), and protein efficiency rate (PER) significantly increased with increasing the dietary lipid level at the same crude protein level, while feed conversion ratio (FCR) and hepatosomatic index significantly decreased (P<0.05). At the same lipid level, there was no difference in WG, FCR, PR, PER between 44% and 49% crude protein group (P>0.05). The P49/L14 group had the highest WG (374.6%) and lowest FCR (1.25), while P44/L14 group had the highest PER (1.80) and PR (25.06%) with similar WG and FCR to P49/L14 group. The crude lipid contents in whole fish were significantly higher in the L14 group than those in the L4 and L9 groups (P<0.05). Muscle n-3 PUFAs, n-6 PUFAs, and PUFAs levels were positively correlated with dietary lipid level, while n-6 PUFAs was negatively correlated with dietary protein level. Dietary protein, dietary lipid, and their interaction significantly affected hepatic malondialdehyde (MDA) content, aspartate aminotransferase, lipase (LPS), and fatty acid synthase (FAS) activities (P<0.05). In both P44 and P49 groups, LPS and FAS activities increased with increasing the dietary lipid level. MDA content significantly decreased in the P44 group and increased in the P49 group with increasing the dietary lipid level (P<0.05). As dietary protein level increased, serum total cholesterol level increased, while hepatic phosphoenolpyruvate carboxykinase activity decreased. With increasing the dietary lipid level, total superoxide dismutase, catalase, total nitric oxide synthase, and fructose-1,6-bisphosphatase activities showed an increasing trend, while the opposite was true for alanine aminotransferase activity. In conclusion, based on growth performance and feed utilization, dietary protein level of 44% and dietary lipid level of 14% (measured value, 43.71% and 13.62%) were suggested for young triploid rainbow trout.